Research Philosophy in Development Studies: An Inquiry from Qualitative Design - Sapkota, Mahendra (Research Nepal Journal of Development Studies, 2019)
Development studies have got both discourse as well as empirical field of research. This paper presents a synthesis of research methodology and its philosophical settings in the field. It deals with philosophical and methodological approaches from the qualitative research design approach. Then it offers a methodological plural perspective along with the discussion of interpretivism, criticalism and social constructivism. Though this paper is not developed out of an empirical field study, the methodology here employed is the review based reflexive perspective of the author. Discussing the context of grounded theory approach, the paper illustrates how a position of the researcher and the conditionality of the study universe affect each other. The central argument of the paper maintains that in multi-real world the disciplinary approach and single-method inquiry could not go into the depth of the research world. Rather, the realties are complex and often changing rapidly in the given political economic context of development. It is thus a time to look after the methodological approach of development studies.